2014
DOI: 10.18376//2014/v10i1/67243
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Exercise for Blood Pressure Control: a Cross-sectional Survey

Abstract: reported a prevalence rate of 36.6% among elderly individuals which peaks at 49 years in both sexes using 140/90mmHg cutoff point. Thus, prevention and control of high blood pressure has become an important public health concern. There is substantial evidence that pharmacological therapy is effective in the control or prevention of Abstract There is emerging empirical evidence of the efficacy of exercise in blood pressure control, however, little is known about factors limiting exercise engagement in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 37 publications
2
24
3
Order By: Relevance
“…than the finding of our study. 15 The practice of exercise was much lower than in a study done in Brazil by Hallal PC et al 16 The difference found could be due to the lifestyle of the people and culture. The importance of exercise might not be in knowledge.…”
Section: Discussionmentioning
confidence: 79%
“…than the finding of our study. 15 The practice of exercise was much lower than in a study done in Brazil by Hallal PC et al 16 The difference found could be due to the lifestyle of the people and culture. The importance of exercise might not be in knowledge.…”
Section: Discussionmentioning
confidence: 79%
“…Among healthy people, blood pressure self-management behavior was potentially influenced by the factors including knowledge about hypertension and previous education on prevention of hypertension. Good knowledge about hypertension has been reported to correlate with better blood pressure control [23], self-integration [24] and self-care [11]. It also be reported that education benefits the understanding about the prevention and controlling of disease, thereby having better self-care [25].…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Good knowledge of blood pressure control was reported from Southern Iran (25.2%), Armenia (50.23%), Saudi Arabia (54.7%), Pakistan (55%), Brazil (82.3%), and India (27.68%). [6][7][8][9][10][11] A study in India showed 43.6% of good knowledge about lifestyle modification regarding blood pressure control. 12 Similarly, it was 14% in Cameron, 13 47.1% in Nigeria, 14 8.9% in Egypt 6 and 61.39% in Addis Ababa, Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] A study in India showed 43.6% of good knowledge about lifestyle modification regarding blood pressure control. 12 Similarly, it was 14% in Cameron, 13 47.1% in Nigeria, 14 8.9% in Egypt 6 and 61.39% in Addis Ababa, Ethiopia. 7 In Nigeria, 32.7% of the participants were knowledgeable about the use of exercise to control blood pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation